Differences of Gonial Index value in male and female hypertension patients using panoramic radiography - Widiawati, Shely Desia; Sarifah, Norlaila; Oktiani, Beta Widya; Taufiqurrahman, Irham; Sukmana, Bayu Indra (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: This study is aimed to measure the Gonial index (GI) value in male and female hypertensive patients using panoramic radiography. Materials and Methods: This is a comparative analytical research. The sampling technique used was the purposive sampling technique. The sample of this study was primary data from panoramic radiographs of hypertensive patients who had been X-rayed at the Radiology Installation of Ulin General Hospital, Banjarmasin. Results: There was no significant difference in the gonial index (GI) values between men (17.83 mm) and women (19.17 mm), with the size of the right region of the female 20.33 mm and the left of the female 16.67 mm and the size of the right region of the male is 17.03 mm and the left male is 19.97 mm. Conclusion: There was no significant difference between the gonial index (GI) values ​​between women and men, although the decrease of bone density in women is higher than in men.